Biological Activities and Molecular Analysis of Novel Dithiocarbazate Complex Compoundson Glioma Cell Lines - Kh. Awidat, Shaban A. (2005)
The object of research in the exploration of new chemotherapy agents is to kill cancerous cells and not harm the healthy cells. In addition, an effective dose of these agents is essential in conducting clinical studies in the treatment of cancer. In this study, an investigation of the anticancer effects of a group of synthetic compounds on human glioma cell lines was carried out. Initially, 11 compounds were screened using cytotoxicity assays. The most active compounds were found to be derived from bis (S-methyl-I3-N-(2-acetylfuran) dithiocarbazate) (SMDB) and bis (S-benzyl-I3-N-(2-acetylfuran) dithiocarbazate) (SBD4) complexed with zinc, cadmium and platinum ions. The glioma cell lines, A172, U87MG and T98G and normal brain cell line HCN-2, were used in this study. The ICso values of the cell lines treated with the compounds were determined by using (3-4,5-dimethylthiazol-2-yl)-2-5-diphenyltetrazolium bromide (MTT) assay. Tamoxifen was used as a control as it is the current drug of choice in the treatment of brain cancer. From the cytotoxicity assays, it was found that the compounds which showed the most potential are SMDB-Cd and SMDB-Zn. The ICso values for SMDB-Cd on A172, U87MG, T98G and HCN-2 were O.65IJg/ml, O.29IJg/ml, OAlJg/ml, and 1AlJg/ml, while that for SMDB-Zn were at 3.7IJg/ml, 1.76IJg/ml, 2.71Jg/ml and 7lJg/ml, respectively. The ICso values for tamoxifen for the same cell lines were 6.7IJg/ml, 5.3IJg/ml, 6.31Jg/ml and 6IJg/ml respectively. Several methods were employed towards understanding the mechanism of action at the molecular level for SMDB-Cd and SMDB-Zn on glioma cell lines. Tunel assay displayed the typical morphological features of apoptosis cells with condensed and fragmented nuclei at 48 hours. The percentage of apoptotic cells in all treated cells with tamoxifen, SMDB-Zn and SMDB-Cd were significantly (p<O.05) increased. Reverse Transcription-Polymerase Chain Reaction (RT-PCR) was used in monitoring the gene expression level of two key genes, Epidermal Growth Factor Receptor (EGFR) and Mouse Double Minute 2 (MDM2). The expression of EGFR gene was suppressed in all three-cell lines. However, MDM2 gene was suppressed only in A172 and T98G. Therefore, the suppression of EGFR and MDM2 by the compounds was one of the pathways to apoptosis in the glioma cells.In the flow cytometry analysis, the effect of SMDB-Cd and tamoxifen on the cell cycle after 3, 6, 12 and 24 hr treatment showed glioma cells A172, U87MG and T98G were arrested in G1 phase and the SMDB-Zn arrested glioma cell lines U87MG, T98G and A172 in, G2/M, S phase and G1 phase, respectively. The SMDB-Cd and tamoxifen arrested the cell cycle by preventing replication (phase specific G1 ) whereas SMDB-Zn was not phase specific which can arrest the cell at any point in the cell cycle. Results, of caspase-8/9 activity assay of tamoxifen, SMDB-Cd and SMDB-Zn on glioma cells showed that caspase-8 activity was significantly induced but no significant activity for caspase-9 was observed. Therefore, the activation of caspase-8 may be the mechanism through which tamoxifen, SMDB-Cd and SMDB-Zn induces apoptosis. The comet assay used to study the genotoxic activity of SMDB-Cd and SMDBZn in CHO cell line showed no genotoxic activity in both compounds. In conclusion, the two compounds have the potential to be developed as chemotherapeutic agents. Nilai ICso untuk sel-sel tersebut yang telah dirawat dengan sebatian-sebatian di-atas dipastikan dengan menggunakan kaedah (3-4, 5-dimethylthiazol-2-yl)-25- diphenyltetrazolium bromide (MIT). Tamoksifen telah digunakan sebagai kawalan memandangkan ia adalah dadah pilihan semasa dalam rawatan kanser otak. Dari kaedah sitotoksik itu sebatian-sebatian yang ditemui menunjukkan potensi adalah SMDB-Cd dan SMDB-Zn. Nilai ICso untuk SMDB-Cd pada A172, U87MG, T98G dan HCN-2 adalah O.65IJg/ml, O.29IJg/ml, OAlJg/ml, dan 1.4lJg/ml, sementara itu bagi SMDB-Zn adalah 3.7IJg/ml, 1.76IJg/ml, 2.7IJg/ml and 7lJg/ml. Nilai ICso bagi tamoksifen pula untuk sel-sel yang sama tersebut adalah 6.7IJg/ml, 5.3IJg/ml, 6.3IJg/ml and 6lJg/ml. Beberapa kaedah telah dijalankan ke arah memahami mekanisme tindakan SMDB-Cd dan SMDB-Zn tersebut dalam sel-sel glioma pada peringkat molekul. Kaedah Tunel telah menunjukkan ciri-ciri morfologi yang tipikal bagi sel-sel apoptotik dengan nukleusnya yang menjadi padat dan pecah pada 48 jam, peratus sel-sel yang apoptotik dalam semua sel-sel yang dirawat bersama tamoxifen, SMDB-Zn dan SMDB-Cd adalah sangat bermakna (p<O.05). "Reverse Transcription-Polymerase Chain Reaction" (RT-PCR) telah digunakan dalam pemerhatian paras ekspresi gen terhadap dua gen ini, "Epidermal Growth Factor Receptor" (EGFR) dan Mouse Double Minute 2 (MDM2). Ekspresi gen EGFR telah dihalang didalam ketiga-tiga sel yang digunakan.